Sustainable framework for a geostationary satellite control earth station system using parallel configuration - Nur Shazana Abdul Rahman; Nadirah Abdul Rahim (Institute of Advanced Engineering and Science, 2023)
Earth station system plays an important role to ensure that a satellite communication system runs efficiently. Redundancies of the subsystems and regular maintenance planning can improve the earth station system. Organising system affordability can be challenging as more redundancies would acquire more maintenance. Thus, a sustainable framework that considers an earth station system's reliability, cost, and maintainability was modelled. 2-parallel, 3-parallel, and 4-parallel earth station system configurations were studied with five mean time between failures (MTBF). The results showed that an earth station that was configured with 2-parallel configuration provided an optimum reliability system performance though both 3-parallel and 4-parallel configuration provided higher reliability. Moreover, the 2-parallel configuration was also cheaper in terms of operational cost if compared to the 3-parallel and the 4-parallel configurations. Hence, this sustainable framework comprising the reliability and operational cost elements were modelled based on the 2-parallel configuration with the proposed maintenance activities. Moreover, the computed root mean square (RMS) values for both new reliability and new operational cost models yielded smallest values of 20.84% and 22.82% respectively. Thus, these RMS values for both reliability and operational cost models based on 2-parallel configuration are suitable to be applied in the earth station system design.